2013
DOI: 10.1186/1423-0127-20-12
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II SNP interactions and the association with type 1 diabetes mellitus in Bengali speaking patients of Eastern India

Abstract: BackgroundSeveral studies have demonstrated a fundamental role for the HLA in the susceptibility of, or protection to, type 1 diabetes mellitus (T1DM). However, this has not been adequately studied in Asian Indian populations. To assess the frequency of HLA class II (DPA1, DPB1, DQA1, DQB1 and DRB1) associated to susceptibility or protection toT1DM in a Bengali population of India with diabetes.ResultsSingle nucleotide polymorphism study. The HLA genotyping was performed by a polymerase chain reaction followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
1
6
1
Order By: Relevance
“…Other reports, however, deny any impact of INSrs689 polymorphism on risk susceptibility to TIDM [16][17][18][19][20]. The study of Benedek et al [14] that documented the association of T allele with ITD in three Jewish populations failed to prove that association in the Israeli Arabs which highlights the effect of ethnicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other reports, however, deny any impact of INSrs689 polymorphism on risk susceptibility to TIDM [16][17][18][19][20]. The study of Benedek et al [14] that documented the association of T allele with ITD in three Jewish populations failed to prove that association in the Israeli Arabs which highlights the effect of ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this mechanistic theory, risk susceptibility associated with gene polymorphisms is largely affected by ethnic variations including the relative genotype frequency in different populations which varies from one community to another [12,13,16,33,34,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are INS-VNTR and CTLA-4. Together, these two genes confer an inheritable disease risk no larger than 15% (19,20) (25). Also, Cejkova P et al showed that the genotype and allele frequencies of -23 HphI did not differ between T1DM, LADA and T2DM groups and group of healthy subjects in population of the Czech Republic (26).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was estimated that the G → T substitution (rs1271572) in the ERβ promoter prevented transcription factor Yin Yang 1 (YY1) binding and reduced its transcription activity. The TT genotype for rs1271572 was associated with elevated risk for breast cancer in Chinese women and with unfavorable prognosis in Chinese breast cancer patients [ 18 ].…”
Section: Introductionmentioning
confidence: 99%